2015
DOI: 10.1504/ajfa.2015.067837
|View full text |Cite
|
Sign up to set email alerts
|

Volume-herding interaction in the American market

Abstract: This paper examines the existence of herding in the US market. We study the turnover effect on herding movement by modifying the CrossSectional Standard Deviation (CSSD) model and the Cross-Sectional Absolute Deviation (CSAD) model. Results are inconclusive about the presence of herding in the US financial market. However, we find that trading volume can trigger herding. By applying VAR and Granger causality tests, we find a strong link between herding and trading volume in both directions. More particularly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
1
19
1
Order By: Relevance
“…The presence of herding at sectors level was also concluded by Cakan, and Balagyozyan (2016) who found evidence of herding in all sectors of Turkish market and BenSaï da (2017) who detected herding in 10 out of 12 sectors in the U.S market. In addition, the results of this study revealed that the existence of herding at market level is not different before and after the global financial crisis (it was absent during both periods) which is the same conclusion reached by Al-Shboul (2012a) and opposite to the conclusions of Angela-Maria, Maria, and Miruna (2015) and BenSaï da, Jlassi, and Litimi (2015) who claimed that the global financial crisis affected the herding behavior among investors.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The presence of herding at sectors level was also concluded by Cakan, and Balagyozyan (2016) who found evidence of herding in all sectors of Turkish market and BenSaï da (2017) who detected herding in 10 out of 12 sectors in the U.S market. In addition, the results of this study revealed that the existence of herding at market level is not different before and after the global financial crisis (it was absent during both periods) which is the same conclusion reached by Al-Shboul (2012a) and opposite to the conclusions of Angela-Maria, Maria, and Miruna (2015) and BenSaï da, Jlassi, and Litimi (2015) who claimed that the global financial crisis affected the herding behavior among investors.…”
Section: Discussionsupporting
confidence: 72%
“…Many studies, however, claimed that herding is not constant but it's changing over time as reported by Sharma et al (2015) and Curto, Falcã o, and Braga (2017). In addition, the level of herding behavior was found to be changing based on the market conditions of rising and falling (Chiang et al, 2013;Erdenetsogt & Kallinterakis, 2016;Rahman et al, 2015) and before and during the global financial crisis (Al-Shboul, 2012a; BenSaï da, Jlassi & Litimi, 2015). In the Jordanian market, where few studies about herding were conducted, the presence of herding was evidenced by Obaidat (2016), Ramadan (2015), and Nasarudin, Noordin, Law, and Yahya (2017) while no evidence of herding was found by Al-Shboul (2012a) in both conditions of market rising and falling.…”
Section: Evidence Of Herdingmentioning
confidence: 99%
“…More specifically, to investigate the presence of herding behaviour in upward trends and downward trends, further, we divided the whole data into three panels, that is, panel A presents the whole period, panel B presents before the COVID-19 outbreak period and panel C presents after the COVID-19 outbreak period. The normality test shows that all series of market return and CSAD are not normal since their skewness terms are different from 0, and their kurtosis coefficients largely exceed 3 (BenSaïda et al, 2015). Moreover, the CSAD t series are stationary but non-normal and asymmetrical, since their kurtosis largely exceeds the threshold.…”
Section: Resultsmentioning
confidence: 99%
“…In the finance literature, behavioural aspect in investment decision has always been a debatable topic for investors, financial asset managers as well as academic researchers (BenSaïda et al, 2015; Chauhan et al, 2019). Behavioural finance suggests that investors mimic others’ action, especially during the turbulent period of fear, uncertainty and panic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the banking network structure is not a random network; relevant studies show that banking networks have significant scale-free network characteristics [37]. The investment of banks is not completely random, and there may be herd effect [38]. However, the model in this paper can well reflect the risk of the banking system.…”
Section: Conclusion and Discussionmentioning
confidence: 96%